Radiation Protection in Nuclear Medicine - Mattsson, Sr̲en.; Hoeschen, Christoph. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book explains clearly and in detail all aspects of radiation protection in nuclear medicine. After an introductory chapter on the general role of radiation protection, measurement quantities and units are discussed, and detectors and dosimeters, described. Radiation biology and radiation dosimetry are then addressed, with the inclusion of a chapter specifically devoted to biology and dosimetry for the lens of the eye. Discussion of radiation doses to patients and to embryos, fetuses, and children forms a central part of the book. Phantom models, biokinetic models, calculations, and software solutions are all considered, and a further chapter focuses on quality assurance and reference levels. Occupational exposure also receives detailed attention. Exposure resulting from the production, labeling, and injection of radiopharmaceuticals and from contact with patients is discussed and shielding calculations are explained. The book closes by considering exposure of the public and summarizing the "rules of thumb" for radiation protection in nuclear medicine. This is an ideal textbook for students and a ready source of useful information for nuclear medicine specialists and medical physics experts.